The Role of Global and Domestic Shocks for Inflation Dynamics: Evidence from Asia. (31st March 2022) - Finck, David; Tillmann, Peter
Abstract : This article studies inflation dynamics and the output–inflation trade‐off in small open economies. We estimate a series of VAR models for a set of six Asian emerging market economies, in which we identify a battery of domestic and global shocks using sign restrictions. We find that global shocks explain large parts of inflation and output dynamics. A series of counterfactuals support these findings and suggest that the role of monetary policy is limited. We estimate reduced‐form Phillips curve regressions based on alternative decompositions of output into global and domestic components. For most countries, we find a positive and significant correlation between inflation and the fraction of GDP driven by domestic shocks only. While including the output component driven by oil prices seems to 'flatten' the Phillips curve, though the effect is not significant, the component driven by global demand shocks 'steepens' the inflation–output nexus.